Design of Robust PID Controller using Static Output Feedback framework - Goyal J.K.; Aggarwal S.; Sahoo P.R.; Ghosh S.; Kamal S. (My University, 2025)
This paper considers the design of a robust PID controller for higher order MIMO plants. The design problem is first recast into a Static Output Feedback (SOF) controller design problem and then the transformed SOF problem is solved within the framework of Linear Matrix Inequalities (LMIs) through a decomposition of the Lyapunov matrix variable. Sufficient LMI criteria are derived that ensure H8 performance of the underlying system. By means of a numerical example, it is shown that the designed controller yields less conservative results. Also, a comparative study is done with the existing techniques to demonstrate the efficacy of the proposed method. © 2020, IFAC (International Federation of Automatic Control) Hosting by Elsevier Ltd. All rights reserved.